An efficient miniature 120 Hz pulse tube cryocooler using high porosity regenerator material. (December 2017) - Yu, Huiqin; Wu, Yinong; Ding, Lei; Jiang, Zhenhua; Liu, Shaoshuai
Highlights: A 1.22 kg coaxial miniature pulse tube cryocooler is designed and tested. A newest regenerator matrix material is fabricated and tested. The comparisons of different meshes stainless steel screen are proposed. A cooling power of 2 W at 80 K is achieved with 55 W input electric power. Abstract: A 1.22 kg coaxial miniature pulse tube cryocooler (MPTC) has been fabricated and tested in our laboratory to provide cooling for cryogenic applications demanding compactness, low mass and rapid cooling rate. The geometrical parameters of regenerator, pulse tube and phase shifter are optimized. The investigation demonstrates that using higher mesh number and thinner wire diameter of stainless steel screen (SSS) can promote the coefficient of performance (COP) when the MPTC operates at 120 Hz. In this study, the 604 mesh SSS with 17 μm diameter of mesh wire is constructed as filler of regenerator. The experimental results show the MPTC operating at 120 Hz achieves a no-load temperature of 53.5 K with 3.8 MPa charging pressure, and gets a cooling power of 2 W at 80 K with 55 W input electric power which has a relative Carnot efficiency of 9.68%.